Kaiken annan - Kamu, Ona, 1967-; Witikka, Pekka; Warner Music Finland ([Kustannuspaikka tuntematon] : Fazer Records, 1997)
2 kappaletta.
Ona Kamu (lauluääni), yhtye.
[Äänite]
Keywords: Kamu, Ona, -- 1967- -- singlet; popmusiikki